Muscle Glycogen in Elite Soccer – A Perspective on the Implication for Performance, Fatigue, and Recovery - Mohr, Magni; Vigh-Larsen, Jeppe F.; Krustrup, Peter (Frontiers in Sports and Active Living, 2022)
Based on extrapolation of current trends in modern soccer, physiological loading has increased markedly, and the game will continue to become even more demanding in the future, which will exacerbate fatigue at the end of a game and between games. Soccer is a glycogen consuming activity due to its high-intensity intermittent nature, and muscle glycogen is a key factor associated with fatigue late in a game, as well as in determining recovery after a game or an intense training session. Low glycogen in individual muscle fibers and subcellular compartments in the muscle cell is likely to negatively affect several essential steps in the excitation-contraction coupling such as action potential propagation, calcium handling and cross-bridge cycling through reductions in muscle ATP which are suggested sites of muscle function impairment inducing muscle fatigue. Recovery of physical performance and muscle glycogen after a soccer game is a slow process, which challenges the reality in modern elite soccer with increased game and training frequency and physiological loading. We suggest a markedly higher prioritization of fitness training modalities, nutritional approaches and general recovery strategies that optimizes muscle glycogen storage prior to games and training sessions. Also, the soccer community including the governing bodies of the sport must acknowledge and plan according to the high and increasing demands of the modern game, as well as the consequences this has on fatigue and recovery. These aspects are paramount to consider in the planning of training and games, as well as in the process of structuring soccer tournaments and developing competitive regulations in the future to optimize performance and player health.